ANALISIS LEVEL KEMAMPUAN NUMERIK SISWA SMA PADA MATERI SISTEM PERSAMAAN LINIER TIGA VARIABEL (SPLTV) - Sri Meylinda, Irma; Solahudin, Iman (Department of Mathematics Education, Universitas Kuningan, 2025)
The numerical ability of Indonesian students is still recorded at a low level. This is based on the results of the Indonesian language mathematics PISA test which also includes a numerical ability test with a score of 403 in 2015 and 396 in This study analyzes students' numerical ability in completing the Three Variable Linear Equation System (SPLTV) material at SMA Negeri 1 Kasokandel. This study uses a qualitative descriptive approach with a case study design, which is a method of analyzing data related to a case. This study involved 30 students of class X-G as subjects. Data were collected through numerical ability tests, interviews, and documentation. The results of the study showed that the level of students' numerical ability was quite good, with most students being able to perform mathematical calculations and solve problems although there were still minor errors that needed to be corrected. Analysis of the forms of problems faced by students showed difficulties in understanding the basic concepts of SPLTV, variable identification, integration of mathematical concepts, verification of solutions, and adaptation to variations in questions. These findings highlight the importance of developing logical thinking skills and conceptual understanding in the learning process. Recommendations provided include the integration of diverse teaching methods by teachers, the provision of adequate educational resources by schools, the development of disciplined study habits by students, and the need for further research to examine other factors that influence students' numerical abilities.